La Visión de América Latina sobre el Reglamento General de Protección de Datos - Enríquez Álvarez, Luis (2020)
25, 2018, most Latin American countries started into a process to reform and create new data protection laws that meet the requirements of the GDPR. However, there are some big challenges considering the technical nature of the GDPR based on a risk-based approach and impact assessments. The need to comply with the new GDPR is essential due to the integration processes and trade agreements between both regions. Most Latin American countries have followed the European vision on the protection of personal data, in contrast to other world powers with lower privacy protection standards. This influence of the European Union in Latin America means that cooperation between the two regions is a must and it will help us to achieve a strategic alliance towards the fourth industrial revolution.